Genetic Code Expansion of Vibrio natriegens - Ozer, Eden; Alfonta, Lital (Frontiers in Bioengineering and Biotechnology, 2021)
Escherichia coli has been considered as the most used model bacteria in the majority of studies for several decades. However, a new, faster chassis for synthetic biology is emerging in the form of the fast-growing gram-negative bacterium Vibrio natriegens. Different methodologies, well established in Escherichia coli, are currently being adapted for Vibrio natriegens in the hope to enable a much faster platform for general molecular biology studies. Amongst the vast technologies available for Escherichia coli, genetic code expansion, the incorporation of unnatural amino acids into proteins, serves as a robust tool for protein engineering and biorthogonal modifications. Here we designed and adapted the genetic code expansion methodology for Vibrio natriegens and demonstrate an unnatural amino acid incorporation into a protein for the first time in this organism.